Evaluation of Osteogenic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cell on Highly Porous Polycaprolactone Scaffold Reinforced With Layered Double Hydroxides Nanoclay - Enderami, Seyedeh Elnaz; Shafiei, Seyedeh Sara; Shamsara, Mehdi; Enderami, Seyed Ehsan; Rostamian Tabari, Abolfazl (Frontiers in Bioengineering and Biotechnology, 2022)
In recent decades, bone tissue engineering has had an effective role in introducing orthopedic implants. In this regard, polymeric scaffolds reinforced with bioactive nanomaterials can offer great potential in tissue engineering implants for replacing bone loss in patients. In this study, the thermally induced phase separation method was used to fabricate three-dimensional highly porous scaffolds made of layered double hydroxide (LDH) /polycaprolactone (PCL) nanocomposites with varied LDH contents ranging from 0.1 wt.% to 10 wt.%. The Phase identification, morphology, and elemental composition were studied using X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy, respectively. Interconnected pores ranging from 5 to 150 µm were detected in all samples. The results revealed that the inclusion of LDH to PCL scaffold reinforced mechanical strength and compressive modulus increased from 0.6418 to 1.3251 for the pure PCL and PCL+LDH (1Wt. %) scaffolds, respectively. Also, thermal stability, degradation rate, and biomineralization especially in comparison with the pure PCL were enhanced. Adhesion, viability, and proliferation of human bone marrow-derived mesenchymal stem cells (hBMSCs) seeded on PCL+LDH scaffolds were improved as compared to the pure PCL. Furthermore, the addition of LDH resulted in the increased mineral deposition as well as expression of ALP and RUNX2 osteogenic genes in terms of differentiation. All in all, our findings revealed that PCL+LDH (1Wt. %) scaffold might be an ideal choice for 3D scaffold design in bone tissue engineering approaches.